Enhancing quality of life among adolescents with bipolar disorder: A randomized trial of two psychosocial interventions. - O'Donnell, L; Axelson, D; Kowatch, R; Schneck, C; Sugar, C; Miklowitz, D (Elsevier, 2017)
Background Adolescents with bipolar disorder (BD) report lower quality of life (QoL) than adolescents with other psychiatric disorders. This study compared the efficacy of family-focused therapy for adolescents (FFT-A) plus pharmacotherapy to brief psychoeducation (enhanced care, or EC) plus pharmacotherapy on self-rated QoL in adolescents with BD over 2 years. Methods Participants were 141 adolescents (mean age: 15.6±1.4yr) with BD I or II who had a mood episode in the previous 3 months. Adolescents and parents were randomly assigned to (1) FFT-A, given in 21 sessions in 9 months of psychoeducation, communication enhancement training, and problem-solving skills training, or (2) EC, given in 3 family psychoeducation sessions. Study psychiatrists provided patient participants with protocol-based pharmacotherapy for the duration of the study. QoL was assessed with The KINDLR Questionnaire (Ravens-Sieberer and Bullinger, 1998) during active treatment (baseline to 9 months) and during a post-treatment followup (9–24 months). Results The two treatment groups did not differ in overall QoL scores over 24 months. However, adolescents in FFT-A had greater improvements in quality of family relationships and physical well-being than participants in EC. For quality of friendships, the trajectory during active treatment favored EC, whereas the trajectory during post-treatment favored FFT-A. Limitations We were unable to standardize medication use or adherence over time. Quality of life was based on self-report rather than on observable functioning. Conclusions A short course of family psychoeducation and skills training may enhance relational functioning and health in adolescents with BD. The effects of different psychosocial interventions on peer relationships deserves further study.